Application of Advanced Numerical Techniques for the Analysis Tubular Adhesive Joints - Eusebio, S. M. L.; Campilho, R. D. S. G. (Technological Innovation in Engineering Research Vol. 3, 2022)
Adhesive joints have been applied in several fields of industry due to their advantages over conventional mechanical fastened or welded joints. Adhesive joints have increased strength, reduced weight and are easier to fabricate. This work consists of a parametric study on the tensile strength of single-lap tubular adhesive joints bonded with three adhesives (Araldite® AV138, Araldite® 2015 and Sikaforce® 7752) and different overlap lengths (LO). The main objective is to evaluate the strength prediction abilities of the eXtended Finite Element Method (XFEM), by comparison with the respective experimental results. A comparison of the results obtained with Cohesive Zone Models (CZM) is also carried out. The parametric numerical study also allows a critical evaluation of the behaviour of the adhesives studied in this type of joint, the distribution of peel (\(σ_y\)) and shear stresses (Txy) for LO=20 and 40 mm and the dissipated energy (Ediss) during the simulations until failure. The XFEM was found to be a viable and accurate method for tubular joint strength prediction when damage initiation and propagation parameters were chosen correctly.